DETERMINAN KEPATUHAN PETANI DALAM MEMBAYAR ZAKAT MELALUI BAITUL MAL GAMPONG - Umuri, Khairil; Syakila, Nadia (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2022)
The purpose of this study was to analyze the effect of knowledge, income, belief, and religiosity on farmer compliance in paying zakat through Baitul Mal Gampong (Study in Bener Meriah Regency) partially and simultaneously. Data of 100 respondents was obtained by distributing questionnaires with purposive sampling technique and analyzed using multiple linear regression method. The results obtained show that the variables of knowledge, income, trust, and religiosity simultaneously have a significant effect on farmers' compliance in paying zakat through Baitul Mal Gampong (Study in Bener Meriah Regency). Knowledge variable has a positive and significant effect, while income, trust, and religiosity have no effect on farmer compliance in paying zakat through Baitul Mal Gampong (Study in Bener Meriah Regency). Therefore, zakat institutions must increase socialization to the public about zakat knowledge and increase trust in zakat institutions.